Audit Komunikasi Pemasaran Motion Radio: Analisis Media Organizational Model melalui Metode Sostac - Anathasia Citra (Humaniora, 2011)
This research is about the marketing communication audit of Otomotion FM that re-branding into Motion Radio by analyzing Media Organizational Model through SOSTAC method, Situation-Objective-Strategy-Tactics-Action-Control. This research is also to see the contribution of Reputation Marketing Strategy to achieve the goals of re-branding, This is a descriptive research with qualitative approach by using in depth interviews by using marketing communication audit format that operates Media Organizational Model and SOSTAC. The result of Marketing Communication Audit shows the effectiveness, strength and weakness of the previous and ongoing marketing communication as a guide to make marketing communications plan and as an input to the marketing communication study because increasingly competitive media business.